Kombinasi Metode Partial Rank Correlation dan Flow Correlation Coefficient untuk Membedakan DDoS dengan Flash Crowds - Calvin Kamtoso; Agustinus Noertjahyana; Rolly Intan (Jurnal Infra, 2021)
With the growing of internet user, causing DDoS attacks to also become more sophisticated. This of course causing DDoS detection became a challenge itself. On the other hand, there is flash crowds which is a traffic generated from a huge amount of valid user. While DDoS attack is becoming more sophisticated, it causes discrimination a DDoS attacks from flash crowds become more challenging.This research will be conducted by combining two methods of partial rank correlation and flow correlation. Partial rank correlation itself can be used to detect low-rate and high-rate DDoS attacks. Meanwhile flow correlation coefficient can be used to discriminate DDoS from flash crowds, albeit it is lacking the capability to detect low-rate DDoS attacks.With the test carried, it can be acknowledged whether combining two methods could produce a program that could detect DDoS, flash crowds, or not. Then whether by combining the two methods could increase the accuracy of detection rate and false positive alarm rate of said program than when each method is run independently.